A Year of Pandemic: Levels, Changes and Validity of Well-Being Data from Twitter. Evidence from Ten Countries - Francesco Sarracino; Talita Greyling; Kelsey J. O'Connor; Chiara Peroni; Stephanié Rossouw (Institute of Labor Economics (IZA), 2021)
In this article, we describe how well-being changed during 2020 in ten countries, namely Australia, Belgium, France, Germany, Great Britain, Italy, Luxembourg, New Zealand, South Africa, and Spain. Our measure of well-being is the Gross National Happiness (GNH), a country-level index built applying sentiment analysis to data from Twitter. We aim to describe how GNH changed during the pandemic within countries, assess its validity as a measure of well-being, and analyse its correlations. We take advantage of a unique dataset of daily observations about GNH, generalised trust and trust in national institutions, fear concerning the economy, loneliness, infection rate, policy stringency and distancing. To assess the validity of the data sourced from Twitter, we exploit various survey data sources, such as the Eurobarometer and consumer satisfaction, and Big Data sources, such as Google Trends. Results indicate that sentiment analysis of tweets can provide reliable and timely information on well-being. This can be particularly useful to timely inform decision-making.
Keywords: C55; I10; I31; H12; 330; happiness; COVID-19; Big Data; Twitter; Sentiment Analysis; well-being; public policy; trust; fear; loneliness